Outbreak of ceftazidime resistance due to a novel extended-spectrum beta-lactamase in isolates from cancer patients. - Naumovski, L (1992)
Ceftazidime is widely used in the therapy of infectious complications in neutropenic patients. We studied an outbreak of ceftazidime-resistant gram-negative bacillary infections in pediatric cancer patients receiving empirical ceftazidime therapy for neutropenic fever. Fourteen isolates (12 Klebsiella pneumoniae and 2 Escherichia coli) from 13 patients were studied. Specimens were obtained from multiple clinical sites including blood, urine, throat, and lung. The organisms were resistant to ceftazidime, aztreonam, and penicillins but remained susceptible to cephamycins and imipenem. All resistant isolates produced a novel beta-lactamase (TEM-26) with a pI of approximately 5.58, which was transferred by transformation to E. coli on a 7.9-kb nonconjugative plasmid which cotransferred resistance to trimethoprim-sulfamethoxazole. This enzyme readily hydrolyzed ceftazidime, aztreonam, and penicillins in a spectrophotometric assay. DNA sequencing data suggest that TEM-26 is derived from TEM-1.